Assessment of Environmental Impacts of Tourismissues, Options and Tools - Bhattacharya, A. K.; Sharma, Ravi; Banerji, Suchitra; Sharma, Kiran (Indian Forester, 2005)
The paper deals with the various issues related to the potential impacts of tourism on the environment. The knowledge gaps in the area have heen identified and research work carried out have been discussed. Different types of the possible environmental impacts and existing models for the assessment of environmental impacts of the tourism activities have been analysed and the research issues have been captured. The methodology and tools for the assessment of environmental impacts of tourism have been suggested.